UJI FITOKIMIA DAN UJI STABILITAS ZAT WARNA DARI EKSTRAK BIJI BUAH ALPUKAT (Persea americana Mill) DENGAN METODE SPEKTROSKOPI UV-VIS - Arifah, Churniati Nur; Saleh, Chairul; -, Erwin (JURNAL ATOMIK, 2016)
The extraction avocado seed (Persea americana Mill) is done by soxhletation method using ethanol 96%. Results soxhletation 146.01 grams powder of avocado seeds obtained 85.76 grams of ethanol extract. Ethanol extracts of avocado seeds concentrated using a rotary evaporator obtained 43.38 grams. Phytochemical results showed that the ethanol extract of avocado seeds contains of compound flavanoid, tannins and anthocyanin. Stability test of the color substance ethanol extracts of  avocado seeds conducted on the influence of 40 oC, 50 oC, 60 oC, 70 oC and 80oC, the influence of pH 3, 4, 5 and 6 and the influence of prolonged storage of 1, 2, 3, 4 and 5 days at a wavelength of 200 to 400 nm. Observation data were analyzed by ANOVA and Duncan test.Keywords: Phytochemicals and color substance stability.